Pengaruh Emotional branding dan Experiential marketing Terhadap Loyalitas Merek Eiger Adventure Melalui Brand trust dan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Eiger Adventure Store Semarang) - Yuda Wijanarka; Sri Suryoko; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
The purpose of this study was to determine the influence of emotional branding, experiential marketing, brand trust and customer satisfaction on brand loyalty of Eiger Adventure. This study uses explanatory research. The sampling technique used nonprobability sampling technique, which is purposive sampling with a sample of 100 people. This research uses analytical quantitative techinques. Data analysis using validity, reliability, correlation coefficient, simple regression, multiple regression, the coefficient of determination, t-test, F-test and path analysis using SPSS 20.0 for Windows. The results showed that emotional branding variables (X1) has mean of 3.80 and a mean respectively experiential marketing variables (X2) is 3.73, brand trust variables (Z1) 3.87, customer satisfaction variable (Z2) 3.83 and brand loyalty variable (Y) of 3.53. Based on the average value, it can be interpreted that the five variables are in high categorization. Results of the analysis showed that emotional branding variable (X1), experiential marketing (X2), brand trust (Z1) and customer satisfaction (Z2) has a positive effect on brand loyalty (Y). Experiential marketing variables are variables that have the greatest influence (0.526) whereas emotional branding variable is a variable that gives the smallest effect (0.043) on brand loyalty. The conclusion of this study shows that emotional branding, experiential marketing, brand trust and customer satisfaction partially or simultaneously affect brand loyalty Eiger Adventure. Based on the results of the Eiger Adventure should improve emotional branding concept, improve the concept of experiential marketing as well as maintain and increase customer confidence and satisfaction. Suggestions for Eiger Adventure is keeping the emotional branding concept and perform various activities to improve the experiential marketing in order to increase confidence in the brand and maintain customer satisfaction products Eiger Adventure.